EVALUASI KUALITAS WEBSITE SEKOLAH SMA NEGERI 6 JAKARTA DENGAN MENGGUNAKAN METODE WEBQUAL 4.0 DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) BERDASARKAN PERSPEKTIF WARGA SEKOLAH - Khodadat Azizy Jeser (2023)
Website is a means to disseminate information by utilizing technology in the form of internet networks. Currently, the majority of schools already have website facilities that are used as a means of distributing information such as announcements, school agendas, and other important information. SMA Negeri 6 Jakarta is one of the schools that has this facility. To measure how good the quality of a school website is, evaluation can be done in the form of a website quality test using the WebQual 4.0 method which is packaged in the form of a questionnaire, in which there are three indicators, namely usability quality, information quality, and service interaction quality. The research was conducted on school residents with a total sample of 346 people divided into several sample groups (Proportional Stratified Random Sampling). This method is combined with the Paired T-test method to prove the truth of the hypothesis and the suitability level test to find out how high the level of agreement is between actual indicators and expectations. The results of the Paired T-test show that the hypothesis is accepted with a significance of 0.000, also the suitability level is not yet close to its peak (92.17%). Followed by actual and expectation quadrant analysis using the Importance Performance Analysis (IPA) method combined with the GAP Analysis method. The results of the combined analysis show that each quadrant has a negative GAP value with an average GAP of -0.3355. Recommendations are given to improve the quality or performance of the website, namely providing redesign suggestions and other improvement suggestions based on the results of the analysis which are then realized directly by the school's IT team by rebuilding the school's website.